Improvement of voltage adaptability for decentralised doubly‐fed induction generator wind power system based on nine‐switch converter. Issue 8 (1st April 2022) - Hu, Zhishuai; Ren, Yongfeng; He, Jinwei; Xue, Yu; Yun, Pingping
Abstract: This paper proposes a method to improve the voltage adaptability of doubly fed induction generator (DFIG) wind turbines in a decentralised scenario by incorporating a nine‐switch converter (NSC). With the proposed scheme, the DFIG can realise low voltage ride‐through (LVRT) and continuous operation under the grid voltage harmonic, drop, and rise. The topology of the NSC‐DFIG system is introduced and is used to solve the circuit model. Control strategies for voltage compensation and current compensation are based on the circuit model. The corresponding voltage compensation scheme and the NSC DC voltage control scheme were designed according to the specific capacity configuration of the NSC in this study. To reduce the DC‐side voltage of the NSC, a third harmonic‐injection modulation method and a dynamic modulation ratio allocation strategy were incorporated. Simulations under four power grid voltage conditions were used to validate the scheme. This method can improve the voltage adaptability for decentralised DFIG wind power systems, which can enable their successful interactions with the power grid.